A model of ventilation used to interpret newborn lamb respiratory signals - Le Rolle, Virginie (IEEE Service Center, 2008)
This paper presents a model-based method for the analysis of respiratory signals specifically adapted to newborns. The model includes a description of upper airways, distensible and lower airways, lungs, chest wall, alveoli, pleura and respiratory muscle activity. The model was used in stationary and non-stationary conditions to simulate respiratory signals obtained in one newborn lamb in various physiological conditions. An identification algorithm was used to adapt the model parameters to lamb data. Finally, the identified parameters were compared to values previously reported in adult humans.